Prospective study on quantitative evaluation of femoral neck bone mineral density using spectral localizer radiograph from photon-counting detector CT - ZHOU Shanshui, QIN Le, CHANG Rui, DU Lianjun, YAN Fuhua, LIU Fangtao (Zhenduanxue lilun yu shijian)
Objective To evaluate the performance of spectral localizer radiograph (SLR) acquired by photon-counting detector CT (PCD-CT) for the quantitative assessment of areal bone mineral density (aBMD) in the femoral neck. Methods From July 2024 to April 2025, subjects (≥18 years old) scheduled for both dual-energy X-ray absorptiometry (DXA) and CT scans were prospectively enrolled. All subjects underwent PCD-CT examinations to obtain SLR, and two observers independently performed blinded measurements of the aBMD in the left femoral neck on the SLR. The measurement results of DXA were used as the reference standard to evaluate the quantitative accuracy of SLR for aBMD and its diagnostic performance for abnormal bone mass (T-score<-1.0). Results A total of 63 subjects (36 females) were enrolled, with a mean age of 64.30±13.20 years. The median aBMD measured by DXA was 0.889 [interquartile range (IQR), 0.749-1.031] g/cm2, and 23 subjects (36.51%) showed abnormal bone mass. The aBMD values measured by the two observers were 0.879 (0.760-0.985) g/cm2 and 0.891 (0.784-0.977) g/cm2, respectively. SLR-based measurements of aBMD demonstrated excellent inter-observer agreement (intraclass correlation coefficient = 0.98). Using DXA results as the reference, the median absolute percentage error of aBMD measured by SLR was 6.66% (IQR, 3.64%-9.80%). The diagnostic accuracy, sensitivity, and specificity of SLR for diagnosing abnormal bone mass were 95.24% (50/63), 95.65% (22/23), and 95.00% (38/40), respectively. Conclusions Spectral localizer radiographs acquired by PCD-CT can accurately quantify bone mineral density in the femoral neck and demonstrate high diagnostic performance for abnormal bone mass.